Encephalitozoon cuniculi Genotype II Concentrates in Inflammation Foci - Brdíčková K; Sak B; Holubová N; Květoňová D; Hlásková L; Kicia M; Kopacz; Kváč M (Dove Medical Press, 2020)
Klára Brdíčková,1,2 Bohumil Sak,3 Nikola Holubová,3,4 Dana Květoňová,3 Lenka Hlásková,3 Marta Kicia,5 Żaneta Kopacz,5 Martin Kváč3,4 1Department of Clinical Microbiology, Bulovka Hospital, Prague, Czech Republic; 2Faculty of Science, University of South Bohemia in České Budějovice, České Budějovice, Czech Republic; 3Institute of Parasitology, Biology Centre, Czech Academy of Science, České Budějovice, Czech Republic; 4Faculty of Agriculture, University of South Bohemia in České Budějovice, České Budějovice, Czech Republic; 5Department of Biology and Medical Parasitology, Wroclaw Medical University, Wroclaw, PolandCorrespondence: Bohumil SakInstitute of Parasitology, Branišovská 31, České Budějovice 37005, Czech RepublicTel +420387775421Fax +420385310388Email casio@paru.cas.czBackground: Microsporidia of the genus Encephalitozoon are generally connected with severe infections with lethal outcome in immunodeficient hosts. In immunocompetent hosts, microsporidiosis typically establishes a balanced host–parasite relationship that produces minimal clinically overt disease. Although the alimentary tract represents one of the main primary target tissues, the mechanisms of reaching other tissues during systemic microsporidian infections remain unclear.Methods: In the present study, we tested the relation between inflammation induction in immunocompetent and immunodeficient mice and the presence of spores of E. cuniculi genotype II in selected organs and in fecal specimens by using molecular and histology methods.Results: We reported the positive connection between inflammation induction and the significant increase of E. cuniculi genotype II occurrence in inflammation foci in both immunocompetent BALB/c and immunodeficient severe combined immunodeficient (SCID) mice in the acute phase of infection and the re-activation of latent microsporidial infection following inflammation induction in immunocompetent mice.Conclusion: The results imply possible involvement of immune cells serving as vehicles transporting E. cuniculi genotype II purposefully across the whole host body towards inflammation. With increasing number of records of infections, it is necessary to reconsider microsporidia as agents responsible for various pathologies. The elucidation of possible connection with pro-inflammatory immune responses represents an important challenge with consequences for human health and development of therapeutic strategies.Keywords: Encephalitozoon cuniculi, inflammation, targeted migration